The development of Augmented Reality-based learning media to improve students’ ability to understand mathematics concept - Pujiastuti, Heni; Haryadi, Rudi; Arifin, Alif Maulana (Department of Mathematics, Universitas Negeri Semarang, 2020)
This research aims to develop an Augmented Reality-based learning media. This research is a type of development research. The development model used is the ADDIE model, which consists of five stages, namely, analysis, design, development, implementation, evaluation. The results of this study are in the form of cards that have been coded, Augmented Reality applications in Android, and student guide worksheets. The results of the validation of media and material experts indicate that this Augmented Reality-based learning media product is valid and feasible to use. The use of Augmented Reality based learning media in learning activities can improve students understanding of mathematical concept ability. This can be seen from the average n-gain obtained 0.61, which is included in the height category. Each indicator of the concept of understanding also shows big and medium improvement. This Augmented Reality based learning media also gets positive responses from students with an average percentage score of 87.50%.